SPECIES DIVERSITY AND ECOLOGICAL-TROPHIC GROUPS OF PHYTONEMATODES OF POTATO PLANTS (Scientific journal of the Fergana State University, 2024)
The article determines the species composition of nematodes common in the root and near-root soil of a potato plant cultivated on a farm in the village of Bulokboshi, Rishton district, Fergana region, and identifies the fauna and bioecological characteristics of the identified nematodes. . As a result of research, 18 species of plant nematodes were found in the soil of the root and periphery of the potato root. It was noted that the identified phytonematodes belong to 2 subclasses, 3 genera, 9 families and 13 genera. Of the identified genera, a small number of Rhabditi and Tylenchi were found in Dorilaimi. It has been established that 9 species of phytonematodes are found in potato roots, and 18 species around the root. In the soil around the roots, 3 species of phytonematodes were observed in large numbers - Panagrolaimus regidus, Cephalobus persegnus, Aphelenchus avenae.